Composite Liquid Marbles as a Macroscopic Model System Representing Shedding of Enveloped Viruses - Roy, Pritam Kumar; Binks, Bernard P.; Fujii, Syuji; Shoval, Shraga; Bormashenko, Edward (Journal of Physical Chemistry Letters, 2020)
Copyright © 2020 American Chemical Society. A model macroscopic system imitating the entry of viruses into living cells is suggested. The system represents the contact of a composite (core-shell) liquid marble with hydrophobic/hydrophilic particles. Composite liquid marbles are water droplets coated with silicone oil armored with nanometer-sized hydrophobic particles serving as an interfacial model of a living cell. Composite marbles absorbed hydrophilic polymer particles but prevented hydrophobic particles from entering their core. Swallowing of hydrophilic particles by composite marbles resembles the penetration of viruses into living cells. The interfacial mechanism of absorption is suggested.
Keywords: Polymer particles; Hydrophilicity; Composites; Liquids; Hydrophobicity